2017
DOI: 10.1145/3072959.3073691
|View full text |Cite
|
Sign up to set email alerts
|

Fusing state spaces for markov chain Monte Carlo rendering

Abstract: Rendering algorithms using Markov chain Monte Carlo (MCMC) currently build upon two different state spaces. One of them is the path space, where the algorithms operate on the vertices of actual transport paths. The other state space is the primary sample space, where the algorithms operate on sequences of numbers used for generating transport paths. While the two state spaces are related by the sampling procedure of transport paths, all existing MCMC rendering algorithms are designed to work within only one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
6
0
6
Order By: Relevance
“…This paper is a preprint of a SIGGRAPH publication [Pantaleoni 2017]. Concurrent to our work Otsu et al [2017] have developed a novel set of mutations relying on an inverse mapping from path space to primary sample space: while proposing different solutions and mathematical methods, our algorithms share a similar underlying idea. Veach [1997] showed that light transport simulation can be expressed as the solution of per-pixel integrals of the form:…”
Section: Main Contributionmentioning
confidence: 99%
“…This paper is a preprint of a SIGGRAPH publication [Pantaleoni 2017]. Concurrent to our work Otsu et al [2017] have developed a novel set of mutations relying on an inverse mapping from path space to primary sample space: while proposing different solutions and mathematical methods, our algorithms share a similar underlying idea. Veach [1997] showed that light transport simulation can be expressed as the solution of per-pixel integrals of the form:…”
Section: Main Contributionmentioning
confidence: 99%
“…Вторая проблема (невозможность смены стратегии сэмплирования во время маленького шага) служит источником дополнительных артефактов на изображении, поскольку отдельные участки изображения (где MIS-веса далеки от нуля и единицы) строятся разными стратегиями (и зачастую, как следствие, разными цепями Маркова). Для решения этой проблемы в работах [16,37,40] были разработаны гибриды MMLT с методами, работающими в пространстве путей ( [45], [49], [28]). В этих работах ( [16,37,40]) строится обратимый переход между мировым пространством путей и первичным пространством путей, за счёт чего удаётся добиться смены стратегии сэмплирования во время маленького шага.…”
Section: методы на основе Mcmcunclassified
“…На сего-дняшний день MMLT можно считать одним из наиболее эффективных и про-грессивных алгоритмов для расчёта освещённости на основе цепей Маркова. В отличие от более новых алгоритмов, о которых пойдёт речь далее, MMLT (как и PSSMLT) не использует никакой дополнительной информации относительно функции освещения (как это делает, например, метод [28]) и не требует реализа-ции специальных дополнительных операций (как это делают методы [31][32][33]). …”
Section: 2unclassified
“…Работы [31][32][33] посвящены построению гибридного подхода, сочетающе-го в себе сильные стороны MLT в пространстве путей (path sace) и в первичном пространстве путей (Primary Sample Space, PSS). Основная идея данного под-хода в том, чтобы сделать переход между упомянутыми пространствами обра-тимым.…”
Section: 2unclassified
See 1 more Smart Citation